Energy efficient filtering of nonuniform broadcast - Kian-Lee Tan; Yu, J.X. (Proceedings of the 16th International Conference on Distributed Computing Systems, 1996)
In a wireless environment, information is broadcast on communication channels to clients using powerful, battery-operated palmtops. To conserve the usage of energy, the information to be broadcast must be organized so that the client can selectively tune in at the desirable portion of the broadcast. Most of the existing work focus on uniform broadcast. However very often, a small amount of information is more frequently accessed by a large number of clients while the remainder are less in demand. This nonuniform access pattern poses several new issues. In this paper we examine these issues and look at how a nonuniform broadcast can be organized for selective tuning by the clients. We propose several new indexing schemes to facilitate selective tuning. A performance study is conducted to study and demonstrate the effectiveness of the proposed schemes.